Glimmer : how design can transform your business, your life, and maybe even the world. - Berger, Warren (Random House, 2009)
What can we learn from the ways great designers think-and how can it improve our world? In this highly original book by journalist Warren Berger, in collaboration with celebrated designer Bruce Mau, ten groundbreaking principles of design are shown in action-addressing business, social, and personal challenges and improving the way we think, work, and live. Glimmer takes readers on a journey through today's fascinating world of design, where the formerly distinct disciplines of graphic, product, and social design are undergoing "smart re-combinations." In the cutting-edge studios of Mau and other visionaries, everything is ripe for reinvention-including the ways businesses function, children learn, and communities thrive. Designers are solving problems at an unprecedented pace today by using improved technology and the highly practical design principles described in this book, such as "Ask stupid questions," "Make hope visible," "Work the metaphor," "Embrace constraints," and "Begin anywhere." Glimmer inspires readers to apply these same principles to their own life challenges.